PARAMETER BIOLOGI DAN KIMIA KUALITAS AIR MATA AIR DI WILAYAH KERJA PUSKESMAS RAKIT 1 - Siti Munfiah (Jurnal Ilmiah Medsains, 2019)
Healthy water is needed to achieve optimal health status. Unhealthy water can be a medium of disease transmission. Springs are one of the water sources that are widely used by community in the work area of Puskesmas Rakit 1 for hygiene sanitation and drinking water sources. The results of the preliminary study carried out on the springs in Gelang Village showed that springs containing Total Coliform were > 2400 CFU/100 ml which exceeded the quality standard (50 CFU/100 ml). The community also complained that the spring sometimes smelled unpleasant. Odors arising from springs can be caused due to iron and manganese content. This is a survey research with a cross sectional approach. The sampling technique was done by purposive sampling, namely choosing a spring that is used for hygiene sanitation or as a source of drinking water. A sample of 5 springs in each village in the working area of Puskesmas Rakit 1 so that 30 samples of springs were obtained. The results showed that based on the parameters of Total Coliform and manganese (Mn) as many as 25 (83.33%) and 2 (6.67%) springs with quality that did not qualify as water for hygiene sanitation, respectively. A total of 30 (100%) springs with iron (Fe) content are eligible as water for hygiene sanitation purposes. The community must treat water from the spring before it is used to fulfill their daily needs.